Predictive Model for Estimating Prostate Resection Size in Transurethral Resection of the Prostate for Patients with Benign Prostatic Hyperplasia - Okwudli C. Amu; Solomon K. Anyimba (International Journal of Medicine and Health Development, 2024)
Background: Transurethral resection of the prostate (TURP) is widely recognized as the gold standard surgical treatment for patients experiencing bladder outlet obstruction (BOO) due to benign prostatic hyperplasia (BPH). An essential consideration in TURP is determining the amount of tissue resection necessary to achieve a clinical improvement of lower urinary tract symptoms. Objectives: To develop a model for predicting resected prostate weight (RPW) for TURP. Materials and Methods: This was a cross-sectional study involving 187 patients who underwent TURP between January 2016 and July 2017 in a Nigerian hospital. Results: The mean age of the patients was 66.13 years (SD = 8.02). The mean post-void residual urine volume (PVR) was 192.74 mL (SD = 241.88), while the mean transrectal ultrasound scan (TRUS) estimated prostate weight (EPW) was 44.24 g (SD = 18.40). The mean RPW was 27.01 g (SD = 10.80), and the mean International Prostate Symptom Score (IPSS) score was 25.88 (SD = 5.12). A statistically significant positive correlation was observed between RPW and TRUS EPW (r = 0.636, P < 0.001) as well as between RPW and PVR (r = 0.359, P < 0.001). A weak positive correlation was found between RPW and pre-treatment IPSS (r = 0.191, P = 0.023). In a regression model, only TRUS EPW and PVR were significant predictors of the RPW (P < 0.05). Conclusion: It is essential to develop a model for predicting the RPW for TURP. This could significantly aid in surgical planning before the procedure.